Studies in international history : - Bourne, K. (Longmans, 1967)
This collection of essays is presented to W. N. Medlicott, Stevenson Professor of International History in the University of London, at the London School of Economic and Political Science, on the occasion of his retirement. The essays concern nineteenth-and twentieth-century diplomatic history and most of them are detailed, original research monographs,...